Fc-Effector-Independent in vivo Activity of a Potent Influenza B Neuraminidase Broadly Neutralizing Antibody - Ahmed M. Khalil; Michael S. Piepenbrink; Ian Markham; Madhubanti Basu; Luis Martinez-Sobrido; James J. Kobie (Viruses, 2023)
Influenza B virus (IBV) contributes to substantial influenza-mediated morbidity and mortality, particularly among children. Similar to influenza A viruses (IAV), the hemagglutinin (HA) and neuraminidase (NA) of IBV undergo antigenic drift, necessitating regular reformulation of seasonal influenza vaccines. NA inhibitors, such as oseltamivir, have reduced activity and clinical efficacy against IBV, while M2 channel inhibitors are only effective against IAV, highlighting the need for improved vaccine and therapeutics for the treatment of seasonal IBV infections. We have previously described a potent human monoclonal antibody (hMAb), 1092D4, that is specific for IBV NA and neutralizes a broad range of IBVs. The anti-viral activity of MAbs can include direct mechanisms such as through neutralization and/or Fc-mediated effector functions that are dependent on accessory cells expressing Fc receptors and that could be impacted by potential host-dependent variability. To discern if the in vivo efficacy of 1092D4 was dependent on Fc-effector function, 1092D4 hMAb with reduced ability to bind to Fc receptors (1092D4–LALAPG) was generated and tested. 1092D4–LALAPG had comparable in vitro binding, neutralization, and inhibition of NA activity to 1092D4. 1092D4–LALAPG was effective at protecting against a lethal challenge of IBV in mice. These results suggest that hMAb 1092D4 in vivo activity is minimally dependent on Fc-effector functions, a characteristic that may extend to other hMAbs that have potent NA inhibition activity.